The Jakarta Flood Disaster Mapping January 2020 - Afiat Anugrahadi, Khomsiyah, Himmes Fitra Yuda , Novi Triany (International Journal of Advanced Science and Technology, 2020)
Flood is one of the most frequent disasters in Jakarta. Several factors cause such a large flood potential, including climate change, land subsidence, and man-made factors. Climate change is projected to be the cause of rising water and river levels due to increased rainfall. DKI Jakarta, located on the delta plain which is drained by 13 natural rivers and 1,400 km of man-made waterways, is also getting worse by climate change. Jakarta receives water load from the hills in the south, and also from coastal tides, causing extreme flooding approximately every five years in 1996, 2002, 202007, 2013, 2014, 2020. This study aims to determine the distribution of puddle points and variations inundation heights in several regions. The methodology used in this study was to collect location points and questionnaire data from victims who were employees of Trisakti University. The results of the Jakarta flood mapping in 2020 of the flood victims calculated 137 location points spread across the Greater Jakarta area, which is a pool of rainwater with high intensity and long duration with a height of puddles varying from 30-400 cm. 47.4% of the 97 questionnaire data collected revealed that inundation heights included in the adverse category ranged from 0.5 m to 1 m. Residents rely more on the type of allocation of funds originating from their savings (61.9%), 54.6% of residents already have access to assistance, 59.8% of residents are assisted by their family/relatives, the type of assistance most in the form of food and drinks is 49.5%, 42.3% of people affected by floods can recover after the disaster in less than one week, as many as 67% of residents experience varied losses ranging from 1-10 million.